2016
DOI: 10.1111/jade.12115
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Engagement to Create Resilient Communities: How a Collaborative Design Approach can Broker and Mobilise Practitioner–Participant Interaction

Abstract: When conducting research with young people, studies consistently cite the need to establish trust and rapport with participants. However, what frequently goes unreported is how to evolve these often highly fragile research relationships, and the subtle tensions and negotiations that can occur. In this article I reflect on my experience of collaborating with a group of young people, identified by their school teachers as vulnerable and at risk of falling through the educational net post compulsory schooling. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In this article, I present an artefact‐based approach for visually documenting, further analysing and disseminating my practice‐based doctoral fieldwork that protected the anonymity of the participants whilst supporting my exploration of the situational, interactional and tacit dimensions of participation. Whilst acknowledging the critical importance of procedural ethical processes, such as gaining institutional approval to conduct research and observing legislative regulations, I argue, in line with Guillemin & Heggen () and Ellis (), that more practical tools are needed to equip researchers and students when in the field and working with vulnerable participants (see also McAra ). In the case of this study, I collaborated with a group of young people under the age of 16 who had been identified by their school teacher as vulnerable and at risk of not reaching ‘positive’ destinations (defined as being in further or higher education, employment or training) beyond compulsory education, and who were living in an area known for high levels of deprivation.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this article, I present an artefact‐based approach for visually documenting, further analysing and disseminating my practice‐based doctoral fieldwork that protected the anonymity of the participants whilst supporting my exploration of the situational, interactional and tacit dimensions of participation. Whilst acknowledging the critical importance of procedural ethical processes, such as gaining institutional approval to conduct research and observing legislative regulations, I argue, in line with Guillemin & Heggen () and Ellis (), that more practical tools are needed to equip researchers and students when in the field and working with vulnerable participants (see also McAra ). In the case of this study, I collaborated with a group of young people under the age of 16 who had been identified by their school teacher as vulnerable and at risk of not reaching ‘positive’ destinations (defined as being in further or higher education, employment or training) beyond compulsory education, and who were living in an area known for high levels of deprivation.…”
Section: Introductionmentioning
confidence: 89%
“…Visiting the class on a weekly basis, I implemented a five‐phase research design. Firsly, this involved a period of observation where I immersed myself in the classroom and participated in the young peoples’ educational practices, with the aim of building a research relationship with the participants based on trust and rapport (which is outlined in more detail in McAra ). Following this, I facilitated a series of participatory design workshops where the participants created experimental direct animations.…”
Section: The Fieldwork Contextmentioning
confidence: 99%
“…I position this work contextually before I critically reflect on my incremental approach to building and sustaining a research relationship with a group of young people identified by their school teachers as at risk, and the catalysing role creativity played. By transporting the technique of Direct Animation into a participatory design context, my aim was to create a safe space and conduit through which the participants could explore, translate, and narrate their experiences and stories (McAra forthcoming 2016). Using this collaborative mode of filmmaking, I describe how the participants produced metaphorical videography exploring their emotional experiences of education.…”
Section: Introductionmentioning
confidence: 99%